Powerful Avidity with a Limited Valency for Virus-Attachment Blockers on DC-SIGN: Combining Chelation and Statistical Rebinding with Structural Plasticity of the Receptor - Porkolab, Vanessa; Lepšík, Martin; Ordanini, Stefania; St John, Alexander; Le Roy, Aline; Thépaut, Michel; Paci, Emanuele; Ebel, Christine; Bernardi, Anna; Fieschi, Franck (ACS central science, 2023)
The C-type lectin receptor DC-SIGN has been highlighted as the coreceptor for the spike protein of the SARS-CoV-2 virus. A multivalent glycomimetic ligand, Polyman26, has been found to inhibit DC-SIGN-dependent trans-infection of SARS-CoV-2. The molecular details underlying avidity generation in such systems remain poorly characterized. In an effort to dissect the contribution of the known multivalent effects - chelation, clustering, and statistical rebinding - we studied a series of dendrimer constructs related to Polyman26 with a rod core rationally designed to engage simultaneously two binding sites of the tetrameric DC-SIGN. Binding properties of these compounds have been studied with a range of biophysical techniques, including recently developed surface plasmon resonance oriented-surface methodology. Using molecular modeling we addressed, for the first time, the impact of the carbohydrate recognition domains' flexibility of the DC-SIGN tetramer on the compounds' avidity. We were able to gain deeper insight into the role of different binding modes, which in combination produce a construct with a nanomolar affinity despite a limited valency. This multifaceted experimental-theoretical approach provides detailed understanding of multivalent ligand/multimeric protein interactions which can lead to future predictions. This work opens the way to the development of new virus attachment blockers adapted to different C-type lectin receptors of viruses.